Silica lipid hybrid microparticles for the co-encapsulation of linseed oil and coenzyme Q10: Preparation and in vitro characterization. (August 2021) - Huang, Juan; Wang, Lizeng; Li, Nuoyan; Xie, Wenjing; Jiang, Pingfu; Liu, Lu; Chu, Lanling; Zhou, Yang
Abstract: This study investigates the efficiency of silica lipid hybrid (SLH) microparticles in delivering linseed oil and coenzyme Q10 (CoQ10). The SLH microparticles were co-loaded with the lipophilic ingredients using high pressure homogenization and freeze drying, then the solidified samples were characterized by flowability analysis, morphological analysis, X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). The release and simulated digestion behaviors of the synthesized microparticles were analyzed in vitro, and their accelerated oxidation stability was assessed. The obtained results indicate that the SLH microspheres prepared with over 8% silica solution are characterized by irregular granular morphology and have good fluidity. Based on XRD and FTIR analyses, SLH-encapsulated CoQ10 exists in molecular dispersion or dissolved states, and the preparation process induces no chemical changes in the components. The silica particles in the SLH formulation inhibit the in vitro release and simulated digestion of ɑ -linolenic acid and CoQ10. Moreover, the oxidation stability of the SLH microparticles is synergistically enhanced by CoQ10 and linseed oil. Overall, the results indicate that SLH microparticles can be used in the food industry for the encapsulation and delivery of functional bioactive compounds. Highlights: Linseed oil and coenzyme Q10 co-loaded silica lipid hybrid microparticles were fabricated. The silica particles could inhibit the release of linseed oil and coenzyme Q10. Nutrients released from silica lipid hybrid microparticles by Fick diffusion mechanism. Linseed oil and coenzyme Q10 had a synergistic effect on stability.